2008
DOI: 10.1021/om7008028
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Selectivity of Olefin Metathesis Catalysts Bearing Cyclic (Alkyl)(Amino)Carbenes

Abstract: The evaluation of ruthenium olefin metathesis catalysts 4-6 bearing cyclic (alkyl)(amino)carbenes (CAACs) in the cross-metathesis of cis-1,4-diacetoxy-2-butene (7) with allylbenzene (8) and the ethenolysis of methyl oleate (11) is reported. Relative to most NHC-substituted complexes, CAAC-substituted catalysts exhibit lower E/Z ratios (3:1 at 70% conversion) in the cross-metathesis of 7 and 8. Additionally, complexes 4-6 demonstrate good selectivity for the formation of terminal olefins versus internal olefins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(127 citation statements)
references
References 15 publications
5
116
0
6
Order By: Relevance
“…These results showed that (8) and (9) are less selective toward ethenolysis than their first generation equivalents (6) and (7) as consistently reported. First generation catalysts give ethenolysis reaction mixtures that correspond to kinetic product distributions with a selectivity toward ethenolysis products, while second generation catalysts are not kinetically selective but tend to yield reaction mixtures that are closer to thermodynamic product distributions [4,10]. It has been well documented that second generation NHC-based catalysts have better stability and activity toward general metathesis reactions [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results showed that (8) and (9) are less selective toward ethenolysis than their first generation equivalents (6) and (7) as consistently reported. First generation catalysts give ethenolysis reaction mixtures that correspond to kinetic product distributions with a selectivity toward ethenolysis products, while second generation catalysts are not kinetically selective but tend to yield reaction mixtures that are closer to thermodynamic product distributions [4,10]. It has been well documented that second generation NHC-based catalysts have better stability and activity toward general metathesis reactions [14].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it became critical to develop more efficient and selective olefin metathesis catalysts for the commercial use of ethenolysis. Recently, we have reported 35 000 TONs, the highest recorded to date, with newly developed catalyst (21) in collaboration with Grubbs and coworkers [10]. For manufacturing of commodity chemicals, the TON should be at least 50 000 [4].…”
Section: Introductionmentioning
confidence: 98%
“…53,54 The carbene ruthenium complexes 67-69 ( Figure 5.17 The kinetic selectivity of the CAAC-based catalysts was investigated by probing the E/Z diastereoselectivity in the cross metathesis of cis-1,4-diaceto-2-butene with allylbenzene (equation 5.5). 55 Compared to the commercially available Grubbs' catalysts, 67-69 afforded lower E/Z ratios (3:1 at 70% conversion, ~ 2:1 at < 60% conversion). The activity of 69 is significantly higher than that of the more sterically hindered catalysts 67 and 68.…”
Section: Olefin Metathesismentioning
confidence: 97%
“…以 cis-1,4-二乙酰氧基-2-丁烯 32 与烯丙基苯 33 的交叉复分解(crossing metathesis, 简称 CM)反应(Eq. 5)为例 [34] , Grubbs 二代催化 剂 3 和 25 主要生成热力学稳定的 E 构型烯烃 34 [33] , 而 22, 23 和 24 对 Z 构型烯烃产物 35 的选择性明显高于 3 和 25; 另一方面, 24 的活性仍比 22 和 23 的活性高很多, 这说明高的 Z 构型烯烃选择性与催化剂的活性关系不 大, 这很可能是 CAACs 配体固有的属性 [34] . 再以油酸 甲酯 36 的乙烯分解反应为例(Eq.…”
Section: Caacs 配体在烯烃复分解催化剂中的研究 现状unclassified
“…再以油酸 甲酯 36 的乙烯分解反应为例(Eq. 6) [34] , Grubbs 二代催化 剂 3 和 25 对端烯 37 和 38 的选择性也较差(分别为 44% 和 33%) [33] 不可忽视的作用, 不同的膦配体带来的的催化效果也不 同 [36] . …”
Section: Caacs 配体在烯烃复分解催化剂中的研究 现状unclassified